Capacity Development of Research Ethics Administrators: Scoping Review. (October 2022) - Mulondo, Mutshidzi A; Tsoka-Gwegweni, Joyce M; LenkaBula, Puleng; Chikobvu, Perpetual
Capacity development of research ethics committees is generally limited to members, and seldom includes administrators. This study sought to map the capacity development efforts of research ethics administrators. A scoping review was conducted. The literature search yielded 92 potentially relevant records, and further screening yielded 22 studies. The 22 studies were extracted and synthesized; two studies spoke directly on administrators' capacity development, while the remaining 20 focused on the capacity development of committees or of committee members. The two studies which spoke directly on administrators reported about two capacity development efforts targeting administrators in Africa, namely the African Conference for Administrators of Research Ethics Committees, and the West African Bioethics Training Program.